Self-cleaning bait throwing device for red loach breeding - JIANG ZHIZHONG; MA BENHE; CHEN CUIYUN; DENG WEIMING (2022)
The invention relates to a bait throwing device, in particular to a self-cleaning bait throwing device for red loach breeding. The technical problem of the invention is to provide the self-cleaning bait throwing device for red loach breeding, which can realize automatic intermittent blanking and is high in throwing efficiency. According to the technical scheme, the self-cleaning bait throwing device for red loach breeding comprises a base, a shell, discharging pipes, a cover, a first rotating shaft and the like, the shell is connected to the top of the base through bolts, the three discharging pipes are welded to the upper portion of the shell, the cover is connected to the upper rear portion of the shell in a threaded mode, and a first fixing block is welded to the lower portion of the left wall in the shell; the right side of the first fixing block is rotationally connected with a first rotating shaft. Under the action of the motor, the first rotating shaft can drive the throwing device to swing forwards, b